Clothed in the Body Asceticism, the Body and the Spiritual in the Late Antique Era. - Hunt, Hannah (Farnham : Ashgate Pub., 2012)
This book explores religious anthropology and asceticism from its biblical and desert roots and within eastern patristic writers including Ephrem, Pseudo-Macarius and Climacus. Hunt examines the apparent paradox that Jesus' earthly existence and post resurrection appearances are experienced through consummately physical actions and attributes yet some ascetics within the Christian tradition appear to seek to deny the value of the human body, to find it deadening of spiritual life.
Cover; Contents; Acknowledgements; Abbreviations; 1 Introduction; 2 Greek Insights into the Human Person; 3 Biblical Understandings of Flesh, Body and Soul; 4 Desert Teachings on the Body and Asceticism; 5 'Virgins of God': Manly Women and Transvestite Saints; 7 The Syrian Perspective on Asceticism; 8 Key Syrian Sources: Apocrypha and Anonymity; 9 Pseudo-Macarius, Messalianism and Synaesthesia; 10 'Clothed in the Body' as a Metaphor for Incarnation; 11 Heterodox Christologies and the Heresiarchs; 12 Orthodox Patristic Formulations; 13 Conclusion; Bibliography; Index of Biblical Terms.
General Index.
Description based on print version record.
Keywords: Asceticism -- History -- Early church, ca. 30-600.; Human body -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Theological anthropology -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Religion; Human body -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Theological anthropology -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Asceticism -- History -- Early church, ca. 30-600.; RELIGION / Christian Theology / Anthropology; BODY, MIND & SPIRIT / Sacred Sexuality; Electronic books